2007
DOI: 10.1128/jvi.01239-07
|View full text |Cite
|
Sign up to set email alerts
|

Replication-Competent Herpes Simplex Virus 1 Isolates Selected from Cells Transfected with a Bacterial Artificial Chromosome DNA Lacking Only the U L 49 Gene Vary with Respect to the Defect in the U L 41 Gene Encoding Host Shutoff RNase

Abstract: To generate a null U L 49 gene mutant of herpes simplex virus 1 (HSV-1), we deleted from the viral DNA, encoded as a bacterial artificial chromosome (BAC), the U L 49 open reading frame and, in a second step, restored it. Upon transfection into Vero cells, the BAC-⌬U L 49 DNA yielded foci of degenerated cells that could not be expanded and a few replication-competent clones. The replication-competent viral clones derived from independent transfections yielded viruses that expressed genes with some delay, produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
69
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(73 citation statements)
references
References 62 publications
3
69
1
Order By: Relevance
“…HSV strains carrying large deletions in the UL41 gene encoding vhs have been reported to have two particular attributes: cells infected with these viruses form spontaneous SGs late in infection (27,41,74), and virus is unable to block activation of doublestranded RNA-dependent eIF2 kinase (protein kinase R [PKR]) that arises as a result of infection (68,75). In keeping with the first attribute, we demonstrate here that specific removal of vhs endoribonuclease activity also results in spontaneous SG formation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…HSV strains carrying large deletions in the UL41 gene encoding vhs have been reported to have two particular attributes: cells infected with these viruses form spontaneous SGs late in infection (27,41,74), and virus is unable to block activation of doublestranded RNA-dependent eIF2 kinase (protein kinase R [PKR]) that arises as a result of infection (68,75). In keeping with the first attribute, we demonstrate here that specific removal of vhs endoribonuclease activity also results in spontaneous SG formation.…”
Section: Discussionsupporting
confidence: 69%
“…3 support the existence of such a component. We have observed that disruption of SG formation continues to late times postinfection (26), when the endoribonuclease activity of vhs is predicted to be suppressed via the interaction of vhs with VP16 and VP22 (65)(66)(67)(68). Thus, another viral component may be required later in infection to ensure the continued disruption of SG formation.…”
Section: Discussionmentioning
confidence: 99%
“…HSV-1 VHS selectively suppresses expression of PKR in HT1080 cell lines. In order to verify the involvement of the VHS in the control of PKR, HT1080 cells were transfected with plasmids expressing wild-type or catalytically inactive VHS protein under the control of the cytomegalovirus (CMV) promoter either alone or along with plasmids expressing two other tegument proteins, U L 48 (VP16) and U L 49 (VP22), previously reported to regulate the function of VHS (26,29). The cells were harvested 48 h after transfection, and lysates were electrophoretically separated in a denaturing polyacrylamide gel, transferred to nitrocellulose membranes, and probed with antibodies against total and phosphorylated forms of PKR and against GAPDH as a loading control.…”
Section: Resultsmentioning
confidence: 99%
“…The demonstration that neutralization of VHS activity required VP22 emerged from the observation that deletion of the gene encoding VP22 resulted in the selection of mutants defective in RNase activity (32). The evidence that VHS-RNase interacts with ICP27 emerged from studies designed to determine the role of this α protein in the degradation of viral mRNAs (33).…”
Section: Discussionmentioning
confidence: 99%